KEKUATAN KATA SEBAGAI PEMBANGUN KARAKTER REMAJA - Fransisca Suwarti (TRANSFORMATIKA, 2017)
Building characters is very important for a nation’s future. Teenagers as the next generation become our awareness or focus in it. Parents, teachers and societies have responsibilities to build their teenagers’ characters. Words and literature have powerful strength that can be used to build their characters. The parents, the teachers and the societies can use them by choosing some good connotative words. They are used in such a good way, calm and low tone. In addition, teachers at schools can also apply them in writing and speaking skills.Key words: words – literature  -  characters